The F1F3 Recombinant Chimera of Leishmania donovani-Nucleoside Hydrolase (NH36) and Its Epitopes Induce Cross-Protection Against Leishmania (V.) braziliensis Infection in Mice - Alves-Silva, Marcus Vinícius; Nico, Dirlei; de Luca, Paula Melo; Palatnik de-Sousa, Clarisa B. (Frontiers in Immunology, 2019)
Leishmania (V.) braziliensis is the etiological agent of Cutaneous (CL) and Mucocutaneous leishmaniasis (ML) in the New World. CL can be more benign but ML can be severe and disfiguring. Immunity to these diseases include hypersensitivity, an enhanced inflammatory response with strong IFN-γ and TNF-α secretion. Additionally, the production of IL-10 which down modulates the immune response is reduced. The Nucleoside hydrolase (NH36) of Leishmania (L.) donovani is the main antigen of the Leishmune® veterinary vaccine and its F3 domain induces a CD4+ T cell-mediated protection against L. (L.) infantum chagasi infection. Prevention of L. (L.) amazonensis infection requires in contrast an additional CD8+ T cell mediated response induced by the F1 domain. Consequently, the F1F3 recombinant chimera, which contains both domains cloned in tandem, optimized the vaccine efficacy against L. (L.) amazonensis mouse infection. We compared the efficacies of NH36, F1, F3 and the FIF3 chimera against L. (V.) braziliensis mouse infection. The F1F3 chimera increased the NH36 specific IgA and response before and after infection and the IgG and IgG3 levels after challenge. It also induced a 49 % stronger intradermal response to leishmanial antigen (IDR) than NH36 that was positively correlated to the levels of IFN-γ and TNF-α, IgG, IgG2a, IgG2b and IgG3 anti-NH36 antibodies. However, stronger Th1 responses with elevated IFN-γ/ IL-10 and TNF-α/ IL-10 ratios were promoted by the F3 and F1 vaccines and detected in infected controls while the F1F3 chimera promoted the highest IL-10 secretion, which reduced the pathological Th1 response, and characterized the induction of a mixed and/or T-cell regulatory response. We identified the epitopes responsible for these immune responses. The F3 vaccine induced the earliest immunity and after challenge, the F1F3 chimera promoted the highest CD4+ and CD8+ cytokine-secreting T cell responses, and the predominant frequencies of multifunctional CD4+ and CD8+IL-2+TNF-α+IFN-γ+ T cells. Also as observed against L. (L.) amazonensis infection, the F1F3 chimera showed the strongest reduction of the ear lesions sizes induced by L. (V.) braziliensis. Our results confirm the potential use of the F1F3 chimera in a multi-species cross-protective vaccine against L. (V.) braziliensis.